2014
DOI: 10.1038/sc.2014.144
|View full text |Cite
|
Sign up to set email alerts
|

Role of local application of autologous platelet-rich plasma in the management of pressure ulcers in spinal cord injury patients

Abstract: Study design: Prospective clinical case series. Objectives: The objective of this study is to evaluate the local application of platelet-rich plasma (PRP) in relation to pressure ulcers (PrUs) healing on one PrU (case) versus saline dressing on another PrU (control) in the same patient. Setting: Tertiary Level Care Centre, India. Methods: Twenty-five spinal cord injury patients with at least two PrUs were included. All 25 PrUs (case) were grade IV, and PrUs (control) were grade II (n ¼ 11), grade IV (n ¼ 10) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 19 publications
4
28
0
Order By: Relevance
“…2nd week antimicrobial properties can decrease colonization and hence infection rate. In the another study, we have demonstrated that advanced wound therapy using local application of PRP seems to be a promising alternative to standard saline dressing in PrU healing [27]. No major complication was observed with local PRP therapy.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…2nd week antimicrobial properties can decrease colonization and hence infection rate. In the another study, we have demonstrated that advanced wound therapy using local application of PRP seems to be a promising alternative to standard saline dressing in PrU healing [27]. No major complication was observed with local PRP therapy.…”
Section: Discussionmentioning
confidence: 90%
“…Yuan et al showed no adverse effect with PRP treatment in 3 patients with chronic wounds [1]. Singh et al reported no systemic or wound site side effect after PRP treatment in 49 patients [27].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an increase in area size, worsening of tissue healing and decrease in exudate amount were determined. Singh et al performed an experimental study in 2014 with 25 patients and applied SP and PRP to pressure sores . In this study, it was reported that ulcer healing was faster in patients with PRP dressing than patients with SP dressing .…”
Section: Discussionmentioning
confidence: 98%
“…Singh et al performed an experimental study in 2014 with 25 patients and applied SP and PRP to pressure sores . In this study, it was reported that ulcer healing was faster in patients with PRP dressing than patients with SP dressing . In a study conducted by Mazzukko, it was found that almost all of the chronic ulcerss healed after PRP gel wound care compared to ulcer care with SP .…”
Section: Discussionmentioning
confidence: 99%
“…The main uses of PRP in ophthalmology are dry eye, graft-versus-host disease, persistent epithelial defects, corneal ulcers or perforations, burns and post-LASIK syndrome (27,(48)(49)(50). The regenerative potential of platelet-rich products has also been tested in tympanic perforation (51,52), skin lesions (53) -such as skin ulcers of multifactorial etiology: diabetic foot (54-56), pressure ulcers (57,58), venous ulcers (59) and even leprosy ulcers (60)-, vitiligo (61) and androgenetic alopecia (62). In the area of gynecology there are reports of the use of PRP to aid wound healing and recovery in caesarean delivery, vulvovaginal atrophy, benign cervical ectopy and it has also been applied in reproductive medicine and erectile dysfunction (63)(64)(65)(66)(67)(68)(69).…”
Section: Clinical Uses Of Platelet-derived Bio-products and Concerns:mentioning
confidence: 99%